Performance of Balinese Pigs Feed Traditional and Fermented Feed in Sukanadi Farmer Women's Group - Yan Tonga; I Gede Sutapa; Ni Made Yudiastari; Luh Suariani; Desandro T. Ama; Ignasius Ghari Jati (International Journal of Scientific Multidisciplinary Research, 2023)
A study was conducted from April 30, 2023 to June 29, 2023 at the Sukanadi Women Farmers Group (KWT) in Pejarakan Village, Gerokgak Subdistrict, Buleleng Regency, which aimed to determine the performance of Balinese/local pigs treated with traditional feed and fermented feed. This study will test the treatment of feed without fermentation (traditional = T) with fermented feed (F). The feed ingredients used are 70% banana stalks, 20% lamtoro leaves and 10% complete feed (mixture of 25% rice bran, 50% corn flour and 25% concentrate). Each treatment used 5 Balinese/local pigs of weaning age ± 2 months with a weight range of 8-10 kg. The variables observed were initial body weight, body weight gain, ration consumption, final body weight, and ration conversion. Furthermore, the data obtained were analyzed by t-test (paired test) according to Steel and Torrie (1991). Based on the results of the study, it was found that female Balinese/local pigs given fermented feed showed better performance than those given traditional feed. Thus it can be concluded that fermented feed can be applied by the community because it is more effective and efficient with feed formulations consisting of 70% banana stems, 20% lamtoro leaves, and 10% complete feed